Trends in Solar Radiation to the Earth’s Surface: A Systematic Literature Review - Faradiba, Faradiba (Asian Journal of Advanced Research and Reports, 2025)
Solar radiation plays an important role in the Earth's energy balance and climate system. This study uses a Systematic Literature Review (SLR) approach to analyze global trends in solar radiation to the Earth's surface (Downward Surface Radiation/DSR) based on seven selected studies. The results of the study show a consistent increase in DSR values, indicating a significant shift in the global energy balance. This trend is associated with increased atmospheric transparency due to decreased aerosol concentrations, known as the global brightening phenomenon. This increase in surface radiation has broad implications, including accelerated surface warming, changes in the hydrological cycle, and increased risks to health and the resilience of the agricultural sector. These findings emphasize the importance of integrating DSR monitoring into climate policy, spatial planning, and cross-sectoral adaptation strategies to reduce risks and optimize the potential of solar energy for sustainable development.